Pengaruh Literasi Ekonomi terhadap Perilaku Konsumtif Mahasiswa - Ristiliana, Ristiliana; Damayanti, Nela; Wati, Indah; Salmiah, Salmiah (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2024)
This research aimed at finding out the influence of economic literacy toward consumptive levels of Economic Education Department Students at UIN Sultan Syarif Kasim Riau. Quanttative approach was used in this research. 157 Economics Education Department students were the population of this research. The samples were 112 students selected by using random sampling technique. Questionnaire and test were the techniques of collecting data. The data analysis technique uses simple linear regression. The research findings showed that there was a significant influence of economic literacy toward consumptive levels of students. It was shown with the results of robserved higher than rtable (0.326>0.184) and sig. score 0.000 lower than 0.005, and the influence was 10.6%. In conclusion, the more students' economic literacy increases, the rationality in the consumer behavior of economic education department estudents at UIN Sultan Syarif Kasim Riau.Keywords: economic literacy, consumptive levels